Expression, purification, structural and functional analysis of Klebsiella pneumoniae nicotinate nucleotide adenylyltransferase - Daya, Tasvi (My University, 2021)
Ongoing and new nosocomial infections threaten sub-Saharan African regions with their spiking statistics. Almost 50% of patients in health-care settings develop nosocomial infections. Klebsiella pneumoniae is a widespread bacterium recognized for conferring bacterial resistance against most current nosocomial antibiotics. These resistance genes can be contracted by other pathogens promoting an outbreak of hospital infections led by superbugs within Africa. This study focuses on a novel expression, purification and structural analysis of K. pneumoniae Nicotinate nucleotide adenylyltransferase (KpNNAT), an enzyme responsible for cellular metabolism and redox balance. KpNNAT was over-expressed in a pGEX-4T-1 vector with a Glutathione S-transferase (GST) tag and a hexahistidine tag. The enzyme was successfully purified and cleaved using both Glutathione (GSH)-agarose column and a Nickel immobilised metal affinity column (Ni2+ -IMAC) in the presence of thrombin. Expression and purification yielded pure KpNNAT with a wet biomass concentration of 5.5 mg/g of E. coli cells. A dual enzyme activity assay consisting of substrates Nicotinate Mononucleotide (NMN) and Adenosine Triphosphate (ATP) in the presence of alcohol dehydrogenase (ADH) proved that the expressed enzyme was active. Structural characterisation of KpNNAT was achieved by assessing the secondary structure through far-UV circular dichroism (CD), the tertiary structure through tryptophan fluorescence, 8-Anilinonaphthalene-1-sulfonic acid (ANS) binding and methylanthraniloyl-ATP (mant-ATP) binding. The secondary structural analysis revealed a predominant α-helical secondary structure of KpNNAT. Tertiary structural analysis indicated the presence of predominantly buried tryptophan residues that are exposed upon the unfolding of KpNNAT. Upon the binding of substrate ATP and product NAD+ to KpNNAT, displacement of ANS and mant-ATP occurred. These displacement studies further indicated that KpNNAT may experience product inhibition and ligand-induced conformations. Thermodynamic analysis, through isothermal titration calorimetry (ITC), showed that the binding of ATP to KpNNAT is an exothermic, single-site binding event. Data from this study concluded that the KpNNAT active site and structural-water molecules which are present during enzyme catalysation can be exploited for drug design and should be further analysed as a possible target in preventing the spread of ESKAPE pathogen infections within Africa
A research report submitted in fulfilment of the requirements of the degree of Masters in Science to the Faculty of Science, School of Molecular and Cell Biology, University of the Witwatersrand, Johannesburg, 2020
Keywords: Nucleotides